EAP corrective feedback in an EMI setting: Student and teacher beliefs. Issue 59 (September 2022) - Weekly, Robert; Pollard, Andrew; Macpherson, James
Abstract: This study examines the oral corrective feedback (CF) beliefs of Chinese students and English for Academic Purposes (EAP) tutors in an English Medium Instruction (EMI) setting in China. Despite considerable variation in spoken English around the world many EAP tutors tend to correct students' spoken language in relation to native speaker norms, while for students the native model is constructed as the ideal model. This exploratory study looks at listening and speaking classes on an EMI undergraduate preparatory course at a Sino-British University in China. This paper focuses on classes delivered by three different EAP teachers and draws on the beliefs of these teachers and their students, as expressed through interviews. The study revealed variation in students' opinions about CF, with some asserting the limited importance of CF and an acceptance of language variability, with others stressing the importance of accurate language. For their part, the EAP teachers feel it is important to correct students because of language policy, assessment, and student expectations, while also being open to language variation. This paper proposes that CF needs to be reorientated to reflect the changing social environments in which English is spoken, from the current 'form focused correction' to 'meaning focused correction'.